The Influence Of Interpersonal Communication, Organizational Culture And Rewards On Employee Work Performance - Tri Mulyani Kartini; Indra Setiawan; Raniasari Bimanti Esthi (Jurnal Ekonomi, 2024)
Human resources are one of the most important assets for the company to ensure the achievement of company goals. This study aims to determine the effect of interpersonal communication, organizational culture and rewards on the performance of PT JKL employees located in the Delta Silicon Cikarang Industrial Estate. This research uses a quantitative approach. The sampling method used is nonprobability sampling, namely by using a measurement scale, namely a Likert scale. The population in this study was 169 with the number of samples in this study were 119 respondents. Where the number of male respondents was 74 people and 45 women. The data analysis technique used in this study used SPSS. The results of this study prove that all hypothesized relationships are supported. The results of the study prove that there is a positive and significant influence between interpersonal communication variables on work performance variables, interpersonal communication variables on employee work performance variables 1), there is a significant influence between organizational culture variables on employee work performance 2), there is a significant influence between reward variables on employee work performance significant influence between reward variables on employee work performance. Simultaneous test results 3), there is a significant positive influence between interpersonal communication variables, organizational culture and rewards on employee work performance. organizational culture and reward on employee work performance.